2016
DOI: 10.1140/epja/i2016-16028-y
|View full text |Cite
|
Sign up to set email alerts
|

DSAM lifetime measurements for the chiral pair in 194Tl

Abstract: Abstract. Most important for the identification of chiral symmetry in atomic nuclei is to establish a pair of bands that are near-degenerate in energy, but also in B(M 1) and B(E2) transition probabilities. Dedicated lifetime measurements were performed for four bands of 194 Tl, including the pair of four-quasiparticle chiral bands with close near-degeneracy, considered as a prime candidate for best chiral symmetry pair. The lifetime measurements confirm the excellent near-degeneracy in this pair and indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…2. In addition, the calculations showed that all four bands correspond to an angular momentum that has large projections on all three nuclear axes, thus indicating chiral geometry for all four bands [12]. Therefore, these calculations highlight a strong possibility that two chiral systems are formed in 194 Tl.…”
Section: Near-degenerate Bands In 194 Tlmentioning
confidence: 68%
See 2 more Smart Citations
“…2. In addition, the calculations showed that all four bands correspond to an angular momentum that has large projections on all three nuclear axes, thus indicating chiral geometry for all four bands [12]. Therefore, these calculations highlight a strong possibility that two chiral systems are formed in 194 Tl.…”
Section: Near-degenerate Bands In 194 Tlmentioning
confidence: 68%
“…Or perhaps only one chiral system is formed, while the third bands has a different, non-chiral nature. Further study of 194 Tl through DSAM analysis revealed deeper similarities of the observed bands [12], but could not resolve the open questions on their nature. To understand better the πh 9/2 ⊗ νi −n 13/2 bands in this mass region the neighbouring nucleus, 193 Tl, was studied.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Nuclear chirality [2] has been intensively studied, and many chiral nuclei have been identified in the A ≈ 130 mass region (e.g., 131 Ba [3], 133 La [4], 133 Ce [5], 135,136,137,138 Nd [6][7][8][9][10][11], 124,126,128,130 Cs [12][13][14][15][16]), as well as in the A ≈ 190 mass region (e.g., 193,194,195,198 Tl [17][18][19][20][21][22]), in the A ≈ 100 mass region (e.g., 103,105,111,113 Rh [23][24][25][26], 105,107 Ag [27,28]), and in the A ≈ 80 mass region (e.g., 78,80 Br [29,30]), making this motion a more common phenomenon. For a recent review on chirality over the nuclear chart see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…At iThemba LABS, a new chiral symmetry region, the thallium isotopes with mass A ≥ 190 was found. Candidate chiral bands were suggested in 198 Tl [2,3] and then in 194 Tl [4][5][6]. Most importantly, a comparison of the properties in the chiral partner bands in 194 Tl showed that this nucleus is one of the best chiral candidates to date [4].…”
Section: Introductionmentioning
confidence: 99%